In completing the square,
1. Arrange the terms in standard form.
2. Divide all terms by the coefficient of x^2 (the value of a).
3. Move the constant (the value of c) to the right side of the equation.
4. Divide the 2nd term by 2 and square the answer.
5. The answer will be your 3rd term. Add also the answer to the right side of the equation.
6. Copy the first term, copy the sign of the second term and the square root of the third term. For example ---> k^2 - 6k + 9 ----> (k-3)^2
7. To cancel the square, square root both terms
8. The answer must have ± sign
9. Then, find the value of the variable. For example, k-3 = ±3 --> k=3+3 --> k=6 k-3 = -3 + 3 k=0
You must solve for both signs ±